2014
DOI: 10.1007/s13721-014-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards evaluating and enhancing the reach of online health forums for smoking cessation

Abstract: Online pro-health social networks facilitating smoking cessation through web-assisted interventions have flourished in the past decade. In order to properly evaluate and increase the impact of this form of treatment on society, one needs to understand and be able to quantify its reach, as defined within the widely-adopted RE-AIM framework. In the online communication context, user engagement is an integral component of reach. This paper quantitatively studies the effect of engagement on the users of the Alt.Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…On the basis of user activity metrics, we identified another very small group of users that seems to be the most problematic in terms of eHealth literacy. This group, which we, similarly as in some other studies [ 67 ], identified as low-engaged users, has the lowest percentage of highly educated users, lowest percentage of females, is the oldest in comparison with other groups, and has the highest percentage of users with long-term chronic or acute illness. On the one hand, members of this group figure the lowest in terms of validating, understanding, and being smart users of the Internet for health-related information, but on the other hand, they are self-confident and trust in their abilities to recognize quality information and grasp the essence from Internet-obtained health information.…”
Section: Discussionsupporting
confidence: 84%
“…On the basis of user activity metrics, we identified another very small group of users that seems to be the most problematic in terms of eHealth literacy. This group, which we, similarly as in some other studies [ 67 ], identified as low-engaged users, has the lowest percentage of highly educated users, lowest percentage of females, is the oldest in comparison with other groups, and has the highest percentage of users with long-term chronic or acute illness. On the one hand, members of this group figure the lowest in terms of validating, understanding, and being smart users of the Internet for health-related information, but on the other hand, they are self-confident and trust in their abilities to recognize quality information and grasp the essence from Internet-obtained health information.…”
Section: Discussionsupporting
confidence: 84%
“…Stearns et al [ 25 ] noted that the bulk of users in a smoking cessation OHC are made up of short-term users (active for approximately less than 1 week), who, regardless of whether they have high or low activity, tend to be involved in the OHC for personal gain. Long-term users with low activity are noted to have smaller social circles and a stronger interest in particular topics.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted engagement computation can be useful for predicting the retention rate of users in the platform, which is in line with the common bond theory. Specifically, in the future, this metric can become an integral component of OHF thread recommender systems [ 16 ], where suitable threads can be recommended to those users who are more likely to develop personal connections through communication. As noted in the Introduction section, previously proposed metrics of OHF activity, including those that rely on social network analysis tools, have been predominantly used for descriptive purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The key premise here is that OHFs grow through their existing users: every contributed post (that is responded to) fosters user “bonding” and enhances the positive network externalities. Therefore, by identifying, encouraging, and perhaps incentivizing the most engaging content contributors, OHF managers could become more successful at keeping their prohealth online forums growing, achieving a greater impact on people’s health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%